Sistem Pengolahan dan Pemanfaatan Air Limbah Domestik (Studi Kasus Pada PT. X) - Praditya Sigit Ardisty Sitogasa; Erwin Kurniawati; Rizka Novembrianto; Pranandito Wisnu Prabowo (ECOTAS, 2023)
Abstract: PT. X is a nut and bolt industry in Surabaya. PT. X treats their domestic wastewater in the Biofilter WWTP and uses it as water for sprinkling open spaces and green open spaces. This is interesting to learn because it can become material for study in domestic wastewater management systems in the industrial sector. The research method uses a qualitative data analysis approach with primary and secondary data sources. Data was collected through observation, interviews and documentation. The results obtained are the existing conditions of water management, starting from the use of clean water to produce waste water, processing, utilization, and efficiency of waste water utilization. The processing produces recycled water which meets quality standards, so that it can be used as watering open spaces and green open spaces. The efficiency of domestic wastewater utilization reaches 99%, with the benefits obtained, namely being able to reduce the cost of purchasing clean water for irrigation and reduce the volume and load of pollutants in water bodies. Keywords: Biofilter, Domestic Wastewater, Watering